The Ukrainian Crisis and European Security Implications for the United States and U.S. Army - Larrabee, F. Stephen (RAND Corporation, 2015)
In the wake of Russia's annexation of Crimea and attempt to destabilize eastern Ukraine, the United States will have to reexamine the basic premises of its European policy. The requirement that NATO may have to build a more robust deterrence and defense posture in Eastern Europe would require the Army and Air Force to revisit their planning assumptions that have minimized the U.S. military commitments to the region since the end of the Cold War.